Improved synapsis dynamics accompany meiotic stability in Arabidopsis arenosa autotetraploids - Adrián Gonzalo; Aditya Nayak; Kirsten Bomblies (Proceedings of the National Academy of Sciences, 2025)
During meiosis, the correct pairing, synapsis, and recombination of homologous chromosome pairs is critical for fertility of sexual eukaryotes. These processes are challenged in polyploids, which possess additional copies of each chromosome. Polyploidy thus provides a unique context to study how evolution can modify meiotic programs in response to challenges. We previously observed that in newly formed (neo-)polyploids of Arabidopsis arenosa , synapsis defects precede chromosomes associating in aberrant multivalent and univalent configurations. Here, we study synapsis dynamics in genotypes with varying levels of meiotic stability to ask whether efficient synaptic progression is a key component of evolving stable tetraploid meiosis. We develop a method to quantify synapsis dynamics using the progression of foci of the pro-crossover factor HEI10 as a reference. HEI10 initially appears at many small foci before accumulating only at crossover sites. In diploids, this transition begins while significant asynapsis is still present, though it quickly declines as HEI10 accumulates at fewer foci. In neo-tetraploids, suboptimal elongation of synaptic initiation sites and stalled synapsis, perhaps due to defective pairing, occurs before the onset of HEI10 accumulation. In established tetraploids, HEI10 accumulation begins only when synapsis is near complete, suggesting enhanced HEI10/synapsis codynamics (even compared to diploids). Hybrids generated by crossing neo- and established tetraploids exhibit intermediate phenotypes. We find the extent of asynapsis correlates positively with crossover numbers, and the frequency of multivalents and univalents, which can disturb chromosome segregation. Our work supports the hypothesis that improving the efficiency of synapsis is important for evolving polyploid meiotic stability.